The Impact of Flipped Learning on Cognitive Knowledge Learning and Intrinsic Motivation in Norwegian Secondary Physical Education - Ove Østerlie; Ingar Mehus (MDPI AG, 2020)
The purpose of the present study was to examine if and how the introduction of a flipped learning (FL) framework in Norwegian lower and upper secondary school physical education (PE) could affect student situational motivation and health-related fitness knowledge (HRFK). 206 Norwegian students (48% girls) from secondary and upper secondary schools were included in a three-week-long intervention. 85 students were assigned to an intervention group and 121 students to a control group, with the intervention aimed at integrating information communication technology (ICT) through the use of online videos. The results showed a negative motivational change for male students unless the activity changes were placed within an explanatory rationale through FL. The application of FL caused more cognitive knowledge learning, resulting in higher levels of HRFK among both girls and boys. The current research provided valuable insights into Norwegian students' motivation for PE and that cognitive knowledge learning can be affected when integrating the use of ICT in PE.